Sistem Informasi Layanan Kredit UKM Berbasis SMS Gateway - Firliana, Rina; Harini, Dwi; Rahmat A, Anas (Universitas Nusantara PGRI Kediri, 2017)
Importance of credit information Small and Medium Enterprises (SMEs) for society, especially in those who need to develop the business unit in the future, which in the present situation that is difficult to build a business. To obtain credit information most people still have access to resources directly to the sources that provide such information. If the information sought is not found then look for other sources. In search of the required information was not little.Service information system with SMS (Short Message Service) on mobile phone s offer convenience and low cost can reduce the above problems. This service is suitable to be applied in seeking information about credit small and medium enterprises. Despite the above, the study made a Credit Information System Based SMS Gateway Service to provide or provide information about credit Credit Medium Enterprises. So it can be used as one of the alternative ways to obtain information about business credit easily and quickly. The result of this final project design is an SMS Gateway server that works without operator, able to provide information and seek information to the banks in accordance with the information requested by the customer and then sends the information to customers who request such information.